The Implementation of Hello English Smartphone Application in Enhancing Students’ Vocabulary Mastery - Sukmawati Tono Palangngan (Institut Agama Islam Negeri Palopo, 2022)
This research aims to enhance students' vocabulary mastery through Hello English smartphone application. This research applied experimental with one group pre-test post-test design. The population was the students of SMA Muhammadiyah Palopo that consist of five classes. Then, the sample taken were 25 students of class X by using cluster sampling technique. Based on the data analysis, it can be seen that the mean score of the pretest was 52,52 while the mean score of the posttest was 80,64. Furthermore, the significant value of paired sample test was smaller than the significant level (0,000 < 0,05). It means that the H1 was accepted and H0 was rejected. In conclusion, Hello English smartphone application significantly enhanced the students’ vocabulary mastery.